A review of connectivity map and computational approaches in pharmacogenomics. (9th January 2017) - Musa, Aliyu; Ghoraie, Laleh Soltan; Zhang, Shu-Dong; Glazko, Galina; Yli-Harja, Olli; Dehmer, Matthias; Haibe-Kains, Benjamin; Emmert-Streib, Frank
Abstract: Large-scale perturbation databases, such as Connectivity Map (CMap) or Library of Integrated Network-based Cellular Signatures (LINCS), provide enormous opportunities for computational pharmacogenomics and drug design. A reason for this is that in contrast to classical pharmacology focusing at one target at a time, the transcriptomics profiles provided by CMap and LINCS open the door for systems biology approaches on the pathway and network level. In this article, we provide a review of recent developments in computational pharmacogenomics with respect to CMap and LINCS and related applications.